What motivates older adult learners in Poland to study foreign languages in later life? - Agata Słowik-Krogulec (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Older adult cohorts (aged 60 and older) currently represent approximately 24% of the population of Poland. It is expected that by 2050 this proportion will increase to 40.4% of the overall population. The demographic change is also reflected in the continuing widespread popularity of various courses designed for this age group and the resulting rise of the number of Universities of the Third Age and other senior centres. However, in order to offer propitious and motivating learning environment for this age group, more research into the participants’ expectations and goals is needed. Three major findings were identified in this study: (a) older adults take up learning languages in later life in order to communicate while travelling (also with their families who live abroad); to socialise and get to know new people and cultures; to maintain intellectual abilities and to develop cognitively; (b) the instructor and other learners are key components in improving older adults’ motivation; and (c) stereotypes related to senescence and to Foreign Language Geragogy should be challenged to make classes relevant and interesting for this age group.